A Park-Ang damage index-based framework for post-mainshock structural safety assessment. (October 2021) - Kalateh-Ahani, Mohsen; Amiri, Saeed
Abstract: Following an earthquake event, the safety of continued occupancy in terms of whether a mainshock-damaged building could withstand upcoming strong aftershocks is a key question for stakeholders. To answer this question, the residual collapse capacity of mainshock-damaged buildings should be evaluated, and in this way, an accurate assessment of the structural damage inflicted during a mainshock-aftershock sequence is of great importance. Recent studies have shown that energy-based damage measures, which calculate the dissipated energy due to cyclic-plastic deformations, can more accurately reflect the secondary damage induced by aftershocks than deformation-based damage measures. Park-Ang damage index is a combined seismic damage measure that integrates the damage caused by excessive deformations with the damage caused by the cumulative hysteretic energy dissipation. This study presents a framework for assessing the post-mainshock structural safety, in which the quantification of the damage accumulated during a mainshock and the determination of the remaining capacity to sustain strong aftershocks are made based on the Park-Ang damage index. First, residual collapse capacity diagrams are produced by performing incremental dynamic analysis under a suite of selected sequential ground motions. Next, an average diagram is made to find the maximum safe damage index, so that values above this threshold would represent the buildings that are deemed to be unsafe. The proposed framework is applied to a reference four-story steel moment-frame building to investigate its collapse potential and evaluates its structural safety in a hypothetical earthquake scenario. The results of the case study indicate that the proposed framework can effectively help structural engineers to decide on whether a mainshock-damaged building is safe to reoccupy and communicate the final decision in a simple diagram to stakeholders.